THE IMPORTANCE OF STATE BORDER GUARDS’ MORAL VALUES WITHIN THE CONTEXT OF CONTEMPORARY MIGRATION CHALLENGES - Aukštuolytė, Nijolė (Border Security and Management, 2016)
Modern human being lives in a constantly changing global world where one strives to save fundamental priorities of own value system. With regard to rapidly changing geopolitical conditions in the world and migrant crises in the European Union a question of tolerance becomes more and more relevant in a society. The aim of the paper is – by highlighting tolerance position in human value system and its importance in today’s world to assess future State Border Guard Service officers’ level of tolerance and to make suggestions for its deeper education. Research results indicate certain tendencies. Firstly, subjective self - evaluation of respondents tolerance significantly differs from the objective tolerance level which was revealed in the research. The data obtained point out typical respondents‘ overvaluating of their own tolerance level. Secondly, respondents showed a big influence of mass media and social networks. Contemporary migrant crises and its descriptions in different mass media are acknowledged by respondents as factors diminishing, not increasing tolerance. Thirdly, research results make us claim that present tolerance level of our respondents, including future SBGS officers, is poor and should be encouraged.Suggestions: general University politics, lectures attitude of mind and their behaviour play important role in tolerance growth; more attention should be paid to gaining multicultural competencies, fostering authentic thinking and developing empathy to other people.